Antifungal activity of Cosmos caudatus kunth extract on plant pathogens and identification of active constituents - Mohd Salehan, Nazihah (2013)
Increasing concern over adverse environmental effects and decreasing efficacy of synthetic fungicides has brought about the urge for the development of new and natural control alternatives for plant diseases. Thus,extensive exploration on exploitation of plants as natural commercial biopesticides is highly desired. Cosmos caudatus Kunth or locally known as ‘Ulam Raja’ in Malaysia, is a traditional herb to cure and improve human ailments. However, antifungal activity of C. caudatus on plant pathogens has not yet been studied. Crude leaf ethanol extract of C. caudatus was separated into three fractions; hexane, ethyl acetate (EtOAc) and aqueous fractions and screened for their antifungal activity against selected plant pathogens using agar cup method. The EtOAc fraction was shown to be the most active in inhibiting mycelia growth of Phytophthora palmivora, the causal pathogen of black pod of cocoa with percentage inhibition in radial growth (PIRG) of 52.0%. Sporangia germination was recorded the lowest in EtOAc fraction with values of 15.62%. This was further observed in the scanning electron micrographs of P. palmivora treated with EtOAc fraction showing stunted growth and abnormalities in the mycelium with reduced sporangia production. The bio-efficacy of the fractions was further tested on detached cocoa pods. The EtOAc fraction gave the highest inhibition of 57.46% on diameter of lesions. These findings indicated that the EtOAc fraction of C. caudatus leaves possesses fungistatic properties against P.palmivora. Identification of the active antifungal compound(s) was carried out using bioassay guided fractionation by column chromatography technique. The EtOAc fraction was first fractionated into thirteen fractions, in which the first fraction (F1) showed highest inhibition against P. palmivora (PIRG of 54.73%). Fraction F1 was further fractionated into eight sub-fractions (F1-1 to F1-8) and it was found that F1-4, F1-5, and F1-6 as the most active with PIRG of 52.56, 46.92 and 48.05%, respectively. Sub-fraction F1-4 was subjected to Solid Phase Extraction (SPE) and the active constituents were identified using GC-MS analysis. Based on NIST/Wiley data, the compounds suggested to have antifungal activity against P. palmivora were identified as oleic acid [9(Z)-octadecenoic acid] (1), palmitic acid [hexadecanoic acid], 2-hydroxy-1- (hydroxymethyl) ethyl ester (2), nonanal (3), octanal (4), and (Z)-2-decenal (5). These findings are hoped to benefit in the development of biopesticide for the control of black pod disease, which ultimately will have profound effects on crop production and economic values.